ANALISIS WACANA KRITIS PEMBERITAAN TERORISME DI MEDIA MASSA PRANCIS DAN INDONESIA - Oktafiani Herlina (AKADEMI KOMUNIKASI RADYA BINATAMA, 2023)
AbstractTerrorism often gets a large portion of coverage in the French and Indonesian mass media. These two countries are prone to violence, which disrupts security and stability. This research is to dismantle the construction of media ideology so that it can reveal hidden meanings or interests in a text. The French media studied were lemonde.fr, le figaro.fr, and 20minutes.fr. Indonesian online media studied were tempo.co, detik.com, and kompas.com. This study uses Norman Fairclough’s critical discourse analysis models using three important dimensions; text, discourse practice, and sociocultural practice. The result is that both French and Indonesian mass media use global narratives in reporting on terrorism, claiming that Islamic groups are responsible for the radical actions that occur. The three French mass media often mention the perpetrators of the attacks using the diction of followers of ISIS, jihadists, Islamic terrorists, Islamic radical groups, extremists, daesh, or attacker’s nativecountry as part of the attacker’s identity. The Indonesian mass media more specifically stated that terrorists were members of radical Islamic organizations affiliated with ISIS.Keywords : Critical Discourse Analysis, Norman Fairclough, French Media, Indonesian Media, terrorism